Shaping the future of work: what future worker, business, government, and education leaders need to do for all to prosper - Kochan, Thomas A. (New York, 2015)
"Shaping the Future of Work lays out a comprehensive strategy for changing the course the American economy and employment system have been on for the past 30 years. The goal is to create more productive businesses that also provide good jobs and careers and by doing so build a more inclusive economy and broadly shared prosperity. This will require workers to acquire new sources of bargaining power and for business, labor, government, and educators to work together to meet the challenges and opportunities facing the next generation workforce.